Economic Benefits of Studying Economics in Canada: A Comparison of Wages of Economics Majors with Wages in Other Disciplines, Circa 2005 - Akbari, Ather H; Aydede, Yigit (Canadian Journal of Higher Education, 2015)
We compared the wages of economics degree holders with of those in 49 other fields of study using data from the 2006 Canadian population census. At the undergraduate level, economics majors earned the sixth highest average wage in 2005. When demographic controls were applied, they ranked ninth on the salary scale. When we compared the wages in 15 fields that require students to take math courses, economists ranked in the middle, as they also did when working as managers and professionals. When working as business and finance professionals, economists had wages surpassed only by finance majors. At the graduate level, economics majors had a greater wage advantage over all of the other fields except for business majors. These results are useful for Canadian university economics departments that have been experiencing declining enrolments over the past few years. In addition, we hope they will enable students to make more informed choices regarding their academic discipline. The results also highlight the need to direct greater policy attention towards developing mathematical skills among incoming university students as a prerequisite for them to build analytical skills, the demand for which in the labour market has been demonstrated in some Canadian and US studies.